Termodinâmica de buracos negros - Filipe Henrique de Castro Menezes (2021)
The objective of this work is to construct and present the so-called black hole thermodynamics. First, the elements of general relativity necessary for the characterization of black holes are exposed, and then the four laws of classical black hole thermodynamics formulated by J. Bardeen, B. Carter and S. Hawking are constructed. This is followed by an analysis of quantum field theory in curved spaces in the background of a black hole, leading to the formulation of Hawking radiation. Finally, the Hawking radiation energy-moment tensor is obtained for a simplified collapse model, and it is possible to describe its effects on the spacetime geometry.